THz Wireless Transmission Systems Based on Photonic Generation of Highly Pure Beat-Notes - Shi Jia; Xianbin Yu; Hao Hu; Jinlong Yu; Toshio Morioka; Peter U. Jepsen; Leif K. Oxenlowe (IEEE Photonics Journal)
In this paper, a terahertz (THz) wireless communication system at 400 GHz with various modulation formats [on–off keying (OOK), quadrature phase-shift keying (QPSK), 16-quadrature amplitude modulation (16-QAM), and 32-quadrature amplitude modulation (32-QAM)] is experimentally demonstrated based on photonic generation of highly pure THz carriers. The experimental THz wireless photonic transmission system is enabled by the ultrawideband behavior of an antenna-integrated unitraveling-carrier-photodiode-based transmitter and a Schottky mixer-based THz receiver. In the experiment, a phase-correlated optical frequency comb (OFC) is created for photomixing generation of the desired THz carrier frequencies with low phase noise. The OFC allows for the generation of flexibly tunable THz carrier frequencies. The performance of the generated THz carriers is experimentally characterized in terms of phase noise, spectrum purity, tunability, and long-term stability. In the case of generating 400 GHz carrier, the measured timing jitter, linewidth, and long-term stability in the experiment are 51.5 fs, less than 2 Hz, and less than ±1 Hz with 3 hours, respectively. We also theoretically analyze the phase noise of photonically generated THz beat-notes when phase correlation of two optical comb tones is damaged due to their path-length difference. In addition, we demonstrate THz wireless transmission of various modulation formats, including OOK, QPSK, 16-QAM, and 32-QAM at beyond 10 Gb/s in such a system, and the measured bit error rate (BER) performance for all the signals after 0.5 m free-space delivery is below the hard decision forward error correction threshold of 3.8 × 10–3. Furthermore, the influence of THz carrier purity on the system performance is experimentally analyzed with respect to the BER of the THz communication signals.